INOVASI DAN ADAPTASI UMKM: MENGHADAPI TANTANGAN PERSAINGAN DI PASAR PORSEA - Pakpahan, Alwin; Manik, Weld Rezki; Sirait, Nani Ro Anggitasari; Munthe, Fetrit; Simanjuntak, Mika Lestari; Saragih, Tiurma Elita (Jurnal Pengabdian Multidisiplin Indonesia (JUPEMI), 2025)
Micro, Small, and Medium Enterprises (MSMEs) have an important contribution to supporting regional economic growth, including in the Porsea Market area, Toba Regency. However, MSMEs are faced with various challenges, such as limited access to capital, low adoption of digital technology, lack of managerial skills, and dynamic changes in consumer preferences. As a form of real contribution to local economic empowerment, this community service activity is carried out to increase the capacity of MSME actors through a series of training, counseling, and mentoring programs focused on innovation strategies and business adaptation in facing market competition. This activity includes education on product development, social media-based digital marketing, business financial management, and the use of simple technology that supports operational efficiency. The results of the activities show an increase in the understanding and skills of business actors in managing their businesses more professionally and adaptively, including in the application of product innovation, the use of digital platforms for promotion, and more orderly financial records. In addition, the formation of a collaborative network between MSME players is an added value that strengthens the local business ecosystem. This activity is expected to be a sustainable effort to improve the competitiveness of MSMEs in the era of increasingly complex market competition